(untitled) (Bangladesh Journal of Medical Science, 2025)
Objective Detailed knowledge regarding the precise location of infraorbital foramen is necessary to avoid iatrogenic nerve injury during surgery. This study was designed to study the various morphometric measurements of the infraorbital foramen. Materials and methods Infraorbital foramina from fifty dry adult skulls were observed for variations in shape, number, and location to facial bony landmarks and maxillary teeth measured. Results The most common shape of the IOF on the right side was oval (40%), and on the left side of the skull, it was circular (44%). The horizontal diameters of the IOF were higher on left side (3.04±0.75mm in males, 3.26+0.91mm in females) than that of on right side (2.70+0.94mm in males and 2.70+1.15mm) which confirmed to be statistically significant difference. Conclusion There were no significant changes in other dimensions of IOF between male and female skulls and between the right and left sides. However, the distance from IOF to the zygomatico-maxillary suture and to the occlusal plane was noticeably higher in males when compared to females. BJMS, Vol. 24 No. 04 October’25 Page : 1254-1259